FedEx: aligning operations strategy to the company’s mission - Van Mieghem, Jan A. (Henry Stewart Talks, 2018)
Through a discussion of the US Postal Service and FedEx’s operations, this case study explores frameworks for successful operations strategy. By highlighting differences in the organisations’ missions, the case study demonstrates that what is good for one business may not be good for another.